POSTPARTUM BLUES PADA PERSALINAN DIBAWAH USIA DUA PULUH TAHUN - Pratiwi, Kurniasari; Chasanah, Istiani Nur; Martuti, Sri (Faculty of Psychology, Diponegoro University, 2016)
Postpartum blues or baby blues is a feeling of sadness experienced by mothers after childbirth related to the baby. Postpartum blues is like an iceberg that is difficult to detect because there are still many people who do not understand about the event. Nevertheless, postpartum blues not being handled properly is one of the factors precipitating the occurrence of postpartum depression,Â can be fatal for mother and baby. Postpartum blues more common in women who marry in their early age. Indonesia has high percentage of early age marriage in the world (ranked 37) and is the second highest in ASEAN after Cambodia. Based on data, there was increasing number of woman cases delivering labor and having children in the village Panggungharjo Sewon Bantul from year 2013 to 2015. Research objectives are to determine the postpartum blues in labor under the age of 20 years. This study is a descriptive study with retrospective design. The study population consists of women who gave birthÂ under the age of 20 years in the village of Panggungharjo, Sewon, Bantul using total sampling (33 subjects). The result showed that 45.5% of respondents who experienced postpartum blues and 54.5% did not experience postpartum blues.